2016
DOI: 10.3934/mbe.2016012
|View full text |Cite
|
Sign up to set email alerts
|

Competition for a single resource and coexistence of several species in the chemostat

Abstract: We study a model of the chemostat with several species in competition for a single resource. We take into account the intra-specific interactions between individuals of the same population of micro-organisms and we assume that the growth rates are increasing and the dilution rates are distinct. Using the concept of steady-state characteristics, we present a geometric characterization of the existence and stability of all equilibria. Moreover, we provide necessary and sufficient conditions on the control parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(71 citation statements)
references
References 19 publications
0
71
0
Order By: Relevance
“…Thus, the classical chemostat model is unable to reproduce reality even qualitatively and new hypotheses should be considered in order to reconcile the theory and the experimental results. Several mechanisms of coexistence in the chemostat were considered in the literature, such as the intra-and interspecific competition between the species [1,3,5,13,27], the flocculation of the species [9,11,12,14], and the densitydependence of the growth functions [6-8, 10, 21]. Mathematical study of several chemostat-like models can be found in the monograph [25], see also [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the classical chemostat model is unable to reproduce reality even qualitatively and new hypotheses should be considered in order to reconcile the theory and the experimental results. Several mechanisms of coexistence in the chemostat were considered in the literature, such as the intra-and interspecific competition between the species [1,3,5,13,27], the flocculation of the species [9,11,12,14], and the densitydependence of the growth functions [6-8, 10, 21]. Mathematical study of several chemostat-like models can be found in the monograph [25], see also [16].…”
Section: Introductionmentioning
confidence: 99%
“…The biodiversity is also found in biological reactors with a mixture including at least two competitors for one resource, see [19,45]. This has triggered a lot of mathematical research aimed to extend model (1) to bring theory and observations in better accordance. Different mechanisms of coexistence which were proposed in the literature are the intra-and interspecific competition [1,11,28,51], the flocculation [8,9,14,15] and the density-dependence [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This has triggered a lot of mathematical research aimed to extend model (1) to bring theory and observations in better accordance. Different mechanisms of coexistence which were proposed in the literature are the intra-and interspecific competition [1,11,28,51], the flocculation [8,9,14,15] and the density-dependence [32][33][34][35]. Several mathematical models [4,12,13,[23][24][25]30] have attempted to understand the effects of an inhibitor on the competition and the coexistence of species in the chemostat.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations